2011
DOI: 10.1111/j.1540-5907.2011.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Electoral Delegation and the Provision of Public Goods

Abstract: How effectively do democratic institutions provide public goods? Despite the incentives an elected leader has to free ride or impose majority tyranny, our experiment demonstrates that electoral delegation results in full provision of the public good. Analysis of the experimental data suggests that the result is primarily due to electoral selection: groups elect prosocial leaders and replace those who do not implement full contribution outcomes. However, we also observe outcomes in which a minimum winning coali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 76 publications
2
90
0
Order By: Relevance
“…Lab experiments by Walker et al (2000) and Kroll et al (2007) provide suggestive evidence for the link between direct democracy and efficient public good provision under ideal conditions. Furthermore, Hamman et al (2011) find that democratic delegation helps lab subjects avoid the free-rider problem and frequently achieve more efficient and equitable social outcomes. Similar results are also found in psychology experiments (e.g., Wilke et al 1986) As Wibbels (2006) notes, however, work in political economy has laid bare the underlying assumptions of decentralization theories (Weingast 1995) and in many cases has demonstrated that they are not met.…”
Section: The Costs and Benefits Of Decentralizationmentioning
confidence: 99%
“…Lab experiments by Walker et al (2000) and Kroll et al (2007) provide suggestive evidence for the link between direct democracy and efficient public good provision under ideal conditions. Furthermore, Hamman et al (2011) find that democratic delegation helps lab subjects avoid the free-rider problem and frequently achieve more efficient and equitable social outcomes. Similar results are also found in psychology experiments (e.g., Wilke et al 1986) As Wibbels (2006) notes, however, work in political economy has laid bare the underlying assumptions of decentralization theories (Weingast 1995) and in many cases has demonstrated that they are not met.…”
Section: The Costs and Benefits Of Decentralizationmentioning
confidence: 99%
“…6 For the effect of democratically appointed leaders see also Hamman, Weber, andWoon (2011), Corazzini, Kube, Maréchal, andNicolò (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Voters have been shown to use retrospective voting rules (Woon, 2012), so that a concern with re-election gives an incentive for leaders to behave well (Dasgupta, 2009). Voters have also been shown to select more pro-social leaders (Hamman et al, 2011). Other experiments underline another behavioral effect of democracy, which is due to aversion for lying:…”
Section: Literaturementioning
confidence: 99%
“…(Eichenberger & Oberholzer-Gee, 1998). Similarly, Grimalda et al (2008) state that "'institutions' allowing more participation in the process of collective choice lead to more 'socially responsible' behavior in the players" and Hamman et al (2011) state that "democratic delegation helps groups overcome the free-rider problem and generally leads to outcomes that are often both efficient and equitable." Hypothesis 2.…”
Section: Hypothesis 1 [Earned Role]mentioning
confidence: 99%